Generic method to assess transmutation feasibility for nuclear waste treatment and application to irradiated graphite. (May 2023) - Rasson, Mathieu; Fuchs, Julien; Augé, Grégoire; Quéri, Jean-Louis; Laurent, Gérard
Abstract: Graphite-moderated nuclear reactors have already produced more than 250, 000 tons of irradiated nuclear graphite, or i-graphite, world-wide. The sustainability of this technology relies on the end-of-life management of its moderator, which is activated into a long-lived, low or intermediate-level nuclear waste, by neutron fluxes, during operating time. In particular, carbon-14 is created. Nuclear transmutation, enabled by laser-driven particle acceleration, has been envisioned as a potential novel treatment scheme for long-lived nuclear waste. By triggering controlled nuclear reactions with energetic particles, long-lived radio-nuclides could be transformed into short-lived or stable isotopes. Such a system could treat the carbon-14 nuclei trapped within the i-graphite matrix, an isotope which is difficult to isolate by other means. This work performs a quantitative preliminary study of this transmutation scheme, in order to assess its feasibility at an industrial scale. The method used can be transposed to assess any transmutation scheme using a beam of particles directly sent on the material to be treated. First, a nuclear interaction channel which transmutes carbon-14 nuclei without creating new long-lived radio-nuclides is identified. It consists in the choice of a type of particle, among which protons, γ photons and neutrons can all be accelerated by laser–matter interaction; and it is completed by the adequate energy at which this particle must be sent on i-graphite. To that end, the nuclear cross-sections of carbon-12, carbon-13 and carbon-14 are reviewed, neglecting other impurities in i-graphite. Then, based on the interaction channel identification, the energy cost of this scheme is estimated. Protons between 1 and 5 MeV make it possible to transmute carbon-14 without creating any new long-lived activity. However, our result show that, even in this favourable reaction channel, the transmutation energy cost is too high for an i-graphite transmutation scheme to be industrially feasible. Highlights: Huge volumes of radioactive carbon-14 have been produced in nuclear reactors. Here we examine how nuclear transmutation could alleviate the issue. We evaluate its energy cost, to assess its feasibility at an industrial scale. MeV protons can transmute well carbon-14, but the energy cost is still prohibitive.